Increased Risk of Influenza and Influenza-Related Complications Among 140, 480 Patients With Inflammatory Bowel Disease. Issue 2 (18th July 2018) - Tinsley, Andrew; Navabi, Seyedehsan; Williams, Emmanuelle D; Liu, Guodong; Kong, Lan; Coates, Matthew D; Clarke, Kofi
Abstract: Background: Diseases of immune dysregulation are associated with an increased risk of viral infections, some of which may be preventable. To date, there are very limited data on the incidence and risk of influenza and related complications in patients with inflammatory bowel disease (IBD). Furthermore, the impact of immunosuppressive medications on that risk is unclear. Therefore, the aim of this study was to estimate the incidence and severity of influenza infections in IBD patients. In addition, we looked specifically at the effect of medications on influenza risk. Methods: Using the MarketScan Database (January 2008 to December 2011), we conducted a retrospective cohort study to estimate the incidence of influenza and risk of related complications in IBD patients compared with those without IBD. We employed a nested case–control study design to evaluate the potential independent effect of IBD medications on influenza risk. Results: A total of 140, 480 patients with IBD and non-IBD controls were studied. There were 2963 patients with influenza compared with 1941 non-IBD subjects. Inflammatory bowel disease patients had an increased influenza risk compared with those without IBD (incidence rate ratio, 1.54; 95% confidence interval [CI], 1.49–1.63). A higher rate of hospitalizations (162/2994 [5.4%] vs 36/1941 [1.85%]; P < 0.001) was noted. Systemic corticosteroids were found to be independently associated with influenza (odds ratio, 1.22; 95% CI, 1.08–1.38). Conclusions: Inflammatory bowel disease patients had an increased risk of influenza compared with those without IBD and were more likely to require hospitalization. Steroids were the only medication class independently associated with flu risk.